The Valuation of Thinning Efectivity Based on Increment Respond of Natural Forest Log Over Area - Farida Herry Susanty (Journal of Sylva Indonesiana, 2020)
Efforts to increase the natural forest productivity was conducted using several ways one of which is through thinning but the effectiveness is not well known yet. The research aims to evaluate the effectiveness of the application of thinning techniques to logged-over natural forests based on the response of the stand increment. The study design was an 11-year-old logged-over natural forest stand that was carried out systematic thinning, thinning based on built trees and without treatment with a total area of 24 ha. Data collection is done by census inventory of trees with limit diameter of 10 cm per 2 years periodically. Stand conditions in the research plot varied in value range of density (419-510 stems ha-1) and the base plane (22.66-28.20 m2.ha-1) which were not too wide. The results of the calculation of the base plan of the stand shows that systematic thinning yields a larger stand increment (0.78-1.95 m2.ha-1.2th-1) compared to thinning based on built trees and without treatment. Thinning gives more responsive results for the Dipterocarp species group (the increment value is almost twice to normal) compared to non Dipterocarp. Based on the regression analysis, function of time period has correlation between 25-33% to the basal area increment. A systematic thinning technique approach that is more appropriate for increasing stand productivity.